PRODUCTION AND CHARACTERIZATION OF ISOPROPYL MYRISTATE FROM NUTMEG FAT - Adi Wibowo, Prasetyo
Nutmeg is one of the most widely grown plants in Indonesia and contains a lot of myristic acid in the form of trimyristin. However, in Indonesia there is no further process of myristic acid from nutmeg fat into chemical products with higher economic value. One of the products that can be produced from the processing of myristic acid is isopropyl myristate (tetradecanoic acid isopropyl ester) which often used in cosmetics, perfumes, etc. So far, isopropyl myristate is produced by esterification of fatty acids with isopropanol. Fatty acids are obtained by hydrolysis of triglycerides at high pressure and temperature (50 bar, 250-260?C), which requires a large amount of energy and costs. On the other hand, previous study reported that the isopropanolysis of cotton seed oil achieved a gain / conversion of 98.9%. The purpose of this research was to determine the effectiveness of the application of the isopropanolysis method in the reference literature on trimyristin from nutmeg fat. Trimyristin from nutmeg was obtained by soxhlet extraction, distillied, then crystallized. The trimyristin then processed through isopropanolysis with a potassium hydroxide catalyst. So far, no reference has been found regarding the isopropanolysis reaction of trimyristine to isopropyl myristate. In this study, the effect of temperature and raw material ratio on the isopropanolysis yield was also determined. The results showed that the reference method was able to convert trimyristin nutmeg to isopropyl myristate up to 29.9%. Experiments on several types of vegetable oil indicate that the type of substrate greatly affects the effectiveness of this method, correlated with the polarity of the triglyceride substrate. The optimum conditions for the process were obtained at a temperature of 60?C and a raw material ratio of 1:24 with a trimyristin conversion percentage of 29.9%.